Propositional study of a model for quality evaluation in technical memory deposits in a Digital Library implemented in DSpace - Maia, Maria Aniolly Queiroz; Coneglian, Caio Saraiva [UNESP]; Shintaku, Milton (Univ Estadual Campinas - Sistema Bibliotecas, 2023)
Introduction: One of the forms of dissemination of technical memory occurs through Digital Libraries and Digital Repositories. These information environments can be developed and customized from various software. In Brazil, DSpace is one of the main systems used in the creation of Digital Libraries and Institutional Repositories, thus providing opportunities for the representation, dissemination, access and use of the information made available from these tools. Given such relevance, the information available in these information environments needs to be of quality, in order to ensure numerous contributions to organizations, as well as to their users. Objective: Considering the need to ensure the quality of the information available in Digital Libraries, this study aims to propose a model to foster the improvement of the quality of technical memory deposits in Digital Libraries implemented from the DSpace. Methodology: This is a qualitative and descriptive study, which makes use of the bibliographic survey technique in national and international databases. Results: Based on the bibliographic survey it was possible to propose the model of evaluation of the quality of deposits in Digital Libraries developed from the DSpace, thus presenting contributions to improve the quality of the information available in these environments so relevant to the dissemination of knowledge. Conclusion: The proposed model will allow interested parties to evaluate the quality of deposits made in Digital Libraries, especially those created through the DSpace software.
Keywords: Digital libraries; Quality of information; Technical memory; DSpace